Design and Implementation of Electromagnetic Actuation System to Actuate Micro/NanoRobots in Viscous Environment - Abdelaziz, Mostafa (AUC Knowledge Fountain, 2023)
The navigation of Micro/Nanorobots (MNRs) with the ability to track a selected trajectory accurately holds significant promise for different applications in biomedicine, providing methods for diagnoses and treatments inside the human body. The critical challenge is ensuring that the required power can be generated within the MNR. Furthermore, ensuring that it is feasible for the robot to travel inside the human body with the necessary power availability. Currently, MNRs are widely driven either by exogenous power sources (light energy, magnetic fields, electric fields, acoustics fields, etc.) or by endogenous energy sources, such as chemical interaction energy. Various driving techniques have been established, including piezoelectric as a driving source, thermal driving, electro-osmotic force driven by biological bacteria, and micro-motors powered by chemical fuel. These driving techniques have some restrictions, mainly when used in biomedicine. External magnetic fields are another potential power source of MNRs. Magnetic fields can permeate deep tissues and be safe for human organisms. As a result, magnetic fields’ magnetic forces and moments can be applied to MNRs without affecting biological fluids and tissues. Due to their features and characteristics of magnetic fields in generating high power, they are naturally suited to control the electromagnetically actuated MNRs in inaccessible locations due to their ability to go through tiny spaces. From the literature, it can be inferred from the available range of actuation technologies that magnetic actuation performs better than other technologies in terms of controllability, speed, flexibility of the working environment, and far less harm may cause to people. Also, electromagnetic actuation systems may come in various configurations that offer many degrees of freedom, different working mediums, and controllability schemes. Although this is a promising field of research, further simulation studies, and analysis, new smart materials, and the development and building of new real systems physically, and testing the concepts under development from different aspects and application requirements are required to determine whether these systems could be implemented in natural clinical settings on the human body. Also, to understand the latest development in MNRs and the actuation techniques with the associated technologies. Also, there is a need to conduct studies and comparisons to conclude the main research achievements in the field, highlight the critical challenges waiting for answers, and develop new research directions to solve and improve the performance. Therefore, this thesis aims to model and analyze, simulate, design, develop, and implement (with complete hardware and software integration) an electromagnetic actuation (EMA) system to actuate MNRs in the sixdimensional (6D) motion space inside a relatively large region of interest (ROI). The second stage is a simulation; simulation and finite element analysis were conducted. COMSOL multi-physics software is used to analyze the performance of different coils and coil pairs for Helmholtz and Maxwell coil configurations and electromagnetic actuation systems. This leads to the following.: • Finite element analysis (FEA) demonstrates that the Helmholtz coils generate a uniform and consistent magnetic field within a targeted ROI, and the Maxwell coils generate a uniform magnetic gradient. • The possibility to combine Helmholtz and Maxwell coils in different space dimensions. With the ability to actuate an MNR in a 6D space: 3D as a position and 3D as orientation. • Different electromagnetic system configurations are proposed, and their effectiveness in guiding an MNR inside a mimicked blood vessel environment was assessed. • Three pairs of Helmholtz coils and three pairs of coils of Maxwell coils are combined to actuate different size MNRs inside a mimicked blood vessel environment and in 6D. Based on the modeling results, a magnetic actuation system prototype that can control different sizes MNRs was conceived. A closed-loop control algorithm was proposed, and motion analysis of the MNR was conducted and discussed for both position and orientation. Improved EMA location tracking along a chosen trajectory was achieved using a PID-based closed-loop control approach with the best possible parameters. Through the model and analysis stage, the developed system was simulated and tested using open- and closed-loop circumstances. Finally, the closedloop controlled system was concluded and simulated to verify the ability of the proposed EMA to actuate an MN under different trajectory tracking examples with different dimensionality and for different sizes of MNRs. The last stage is developing the experimental setup by manufacturing the coils and their base in-house. Drivers and power supplies are selected according to the specifications that actuate the coils to generate the required magnetic field. Three digital microscopes were integrated with the electromagnetic actuation system to deliver visual feedback aiming to track in real-time the location of the MNR in the 6D high viscous fluidic environment, which leads to enabling closed-loop control. The closed-loop control algorithm is developed to facilitate MNR trajectory tracking and minimize the error accordingly. Accordingly, different tests were carried out to check the uniformity of the magnetic field generated from the coils. Also, a test was done for the digital microscope to check that it was calibrated and it works correctly. Experimental tests were conducted in 1D, 2D plane, and 3D trajectories with two different MNR sizes. The results show the ability of the proposed EMA system to actuate the two different sizes with a tracking error of 20-45 µm depending on the axis and the size of the MNR. The experiments show the ability of the developed EMA system to hold the MNR at any point within the 3D fluidic environment while overcoming the gravity effects. A comparison was made between the results achieved (in simulation and physical experiments) and the results deduced from the literature. The comparison shows that the thesis’s outcomes regarding the error and MNR size used are significant, with better performance relative to the MNR size and value of the error.